Improving Nurse' Knowledge about Elder Abuse - Anung Ahadi Pradana; Rohayati Rohayati; Casman Casman (MITRA: Jurnal Pemberdayaan Masyarakat, 2022)
The incidence of violence in the elderly is suspected to have a very detrimental effect and can reduce the quality of life of the elderly. Several interventions, such as increasing public awareness and health workers, screening the risk of violence, and strengthening the elderly group to be able to report incidents of violence are known to have a positive effect on reducing cases of violence in the elderly. The activity was carried out in the form of increasing knowledge about violence in the elderly virtually for 464 participants consisting of nursing students and professional nurses from 23 provinces. The results of the Wilcoxon test analysis showed a significance value of 0.000 (< 0.05) which indicated a positive benefit in increasing nurses' knowledge about violence in the elderly. Health workers, especially nurses, are still one of the parties trusted by the elderly group to get rid of all the pain and treatment they experience. The implementation of knowledge improvement programs is known to have a positive effect on nurses' knowledge, some limitations that may be considered by researchers or health workers in designing further activities include: the need for full support from policy makers in implementing the program, the need for a program that is sustainable and not only carried out once in a while, and the need for an active role from health workers to participate in finding out about violence in the elderly through several other ways.